2003
DOI: 10.1076/ocii.11.1.39.15578
|View full text |Cite
|
Sign up to set email alerts
|

Splenic T cells from mice receiving intracameral antigen suppress in-vitro antigen-induced proliferation and interferon-? production by sensitized lymph node cells

Abstract: The differential, cytokine-dependent immunoregulatory effects of CD4( +) and CD8(+) AC-spleen cells observed in vitro parallel their effects in vivo. We suggest that the suppression of antigen-induced lymphocyte proliferation and IFN-gamma production by AC-spleen cells provides a useful in-vitro assay of the immunoregulatory activity of cell populations that are induced by the injection of antigen into the anterior chamber.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…This observation was based on a previous finding, demonstrating that CD8 + T‐cell‐mediated suppression in certain models depends upon IFN‐γ production in order to elaborate TGF‐β activity 21 . In addition, CD8 + AC‐SPL cells do produce TGF‐β but do not produce IL‐10 31 . Nevertheless, Kezuka & Streilen reported that CD8 + suppressor T cells are produced in FasL –/– mice 32 .…”
Section: Discussionmentioning
confidence: 95%
“…This observation was based on a previous finding, demonstrating that CD8 + T‐cell‐mediated suppression in certain models depends upon IFN‐γ production in order to elaborate TGF‐β activity 21 . In addition, CD8 + AC‐SPL cells do produce TGF‐β but do not produce IL‐10 31 . Nevertheless, Kezuka & Streilen reported that CD8 + suppressor T cells are produced in FasL –/– mice 32 .…”
Section: Discussionmentioning
confidence: 95%
“…Splenic CD8 + T cells induced by the intracameral injection of antigen suppress the transfer of DTH in vivo by sensitized T cells 6 , 7 , 12 , 14 and antigen‐induced T‐cell proliferation and interferon‐γ (IFN‐γ) production in vitro . 23 , 24 , 25 , 26 The LTS assay measures the suppression of a DTH reaction in immunized recipients by the transfer of CD8 + regulatory T cells but not naive spleen cells to the site challenged by antigen. We used this in vivo demonstration of the suppression of DTH by injected AC‐SPL cells because this is analogous to the suppression of DTH reaction by the injection of antigen into the AC.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of suppression of a DTH reaction by the CD8 + regulatory effector AC‐SPL cells is not known. However, there are reports that suggest that CD8 + regulatory effector cells produce immunosuppressive TGF‐β 23 , 30 , 31 , 32 . The suppression of TCR‐mediated proliferation of T cells in vitro by CD8 + regulatory cells induced by the intracameral injection of antigen is partially inhibited by antibodies to TGF‐β1 32 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TGF-β and IL-10 have been shown to be the suppressive cytokines in immune tolerance models including ACAID [13][14][15][16][17][18][19][20][21][22]. TGF-β1, a major component of the TGF-β family, along with TGF-β2 has been proven to be involved in the immunoregulation.…”
Section: Discussionmentioning
confidence: 99%